Ownership choices of Indian direct investors: Do FDI determinants differ between joint ventures and whollyowned subsidiaries? - Peter Nunnenkamp; Maximiliano Sosa Andrés (Kiel Institute for the World Economy (IfW), 2013)
Using count data on Indian joint ventures (JVs) and wholly owned subsidiaries (WOS), we present an empirical analysis of FDI-related ownership choices and their relation with host country characteristics and indicators of transaction costs. Our Negative Binomial regression models offer only weak support for the bargaining perspective, according to which JVs should be more likely if the host countries were particularly attractive in terms of market access or resource endowments. Geographical and cultural distance has ambiguous effects on the choice between JVs and WOS. The composition of FDI projects tends to shift toward WOS where investment risks are contained by bilateral treaties and better control of corruption.
Keywords: F21; 330; outward FDI; ownership choices; transaction costs; host country characteristics; India